Optimization of localized surface plasmon resonance transducers for studying carbohydrate-protein interactions - Bellapadrona, Giuliano; Tesler, Alexander B; Grünstein, Dan; Hossain, Laila H; Kikkeri, Raghavendra; Seeberger, Peter H; Vaskevich, Alexander; Rubinstein, Israel (Analytical chemistry (Washington), 2012)
Noble metal nanostructures supporting localized surface plasmons (SPs) have been widely applied to chemical and biological sensing. Changes in the refractive index near the nanostructures affect the SP extinction band, making localized surface plasmon resonance (LSPR) spectroscopy a convenient tool for studying biological interactions. Carbohydrate-protein interactions are of major importance in living organisms; their study is crucial for understanding of basic biological processes and for the construction of biosensors for diagnostics and drug development. Here LSPR transducers based on gold island films prepared by evaporation on glass and annealing were optimized for monitoring the specific interaction between Concanavalin A (Con A) and D-(+)-mannose. The sugar was modified with a PEG-thiol linker and immobilized on the Au islands. Sensing assays were performed under stationary and flow conditions, the latter providing kinetic parameters for protein binding and dissociation. Ellipsometry and Fourier transform-infrared (FT-IR) data, as well as scanning electron microscopy (SEM) imaging of fixated and stained samples, furnished independent evidence for the protein-sugar recognition. Enhanced response and visual detection of protein binding was demonstrated using Au nanoparticles stabilized with the linker-modified mannose molecules. Mannose-coated transducers display an excellent selectivity toward Con A in the presence of a large excess of bovine serum albumin (BSA).